Board member nomination and election (Paris, 2012)
"This report addresses the corporate governance framework and company practices that determine the nomination and election of board members. It covers some 26 jurisdictions including in-depth reviews of four jurisdictions: Indonesia, Korea, the Netherlands and the United States."